Pertanggungjawaban Pihak Gojek atas Kerugian yang Diderita Konsumen dalam Hal Penyelenggaraan Pengangkutan Barang - I Made Pratitha Adi Putra; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2021)
The Go-Jek phenomenon is an innovation from the conventional transportation phenomenon because the evidence and / or transportation documents are in the form of electronic documents, so it is necessary to know how the transporter is responsible for losses suffered by consumers (service users) in the transportation of goods by PT. Go-Jek Indonesia and the legal remedies that consumers can take. This study aims to explain the transporter's responsibility for losses suffered by consumers (service users) in the transportation of goods by PT. Go-Jek Indonesia and analyze what laws are done by consumers (service users) to carriers for the losses they have suffered. The type of research used is the type of normative legal research which is carried out by the method of recording and reviewing based on legal materials. Data is obtained by collecting information through legal science books without deviating from positive law in order to form a conclusion, therefore the data source is primary and secondary data. The results showed that the responsibility mechanism for giving compensation to consumers due to the mistakes of business actors, PT. Go-Jek Indonesia provides guarantees and / or guarantees for its services through the terms and conditions listed on its official website which provides a maximum of IDR. 10,000,000, -. Legal remedies that can be taken by consumers against carriers for the damage they have suffered are in accordance with the provisions of the Consumer Protection Law.